Antidepressant and antipsychotic prescribing in primary care for people with dementia - Drummond, Neil (Can Fam Physician, 2018)
OBJECTIVE: To use data from the Canadian Primary Care Sentinel Surveillance Network (CPCSSN) to evaluate the prevalence of antidepressant and antipsychotic prescriptions among patients with no previous depression or psychosis diagnoses, and to identify the factors associated with the use of these drugs in this population. DESIGN: Retrospective cohort study using data derived from CPCSSN. SETTING: Primary care practices associated with CPCSSN. PARTICIPANTS: Patients who were born before 1949; who were associated with a CPCSSN primary care practitioner between October 1, 2007, and September 30, 2013; and whose electronic medical records contained data from at least 6 months before and 12 months after the date of dementia diagnosis. MAIN OUTCOME MEASURES: Prescription for an antidepressant or antipsychotic medication in the absence of a depression or psychosis diagnosis. Multivariable models were fitted to determine estimated odds ratios (ORs) and were adjusted for age and sex. RESULTS: Of the 3252 patients without a depression diagnosis, 8.5% received a new prescription for an antidepressant in the 12 months following their diagnosis of dementia. Prescribing was reduced in association with older age (OR of 0.86 per 5-year age increase, P=.001) and male sex (OR=0.77, P=.056), and prescribing increased in association with prescription of cholinesterase inhibitor medications (OR=1.57, P=.003). Of the 4262 patients without a diagnosis of psychosis, 6.1% received a new prescription for an antipsychotic in the 12 months following their diagnosis of dementia. Higher rates of antipsychotic prescriptions were reported in men (OR=1.31, P=.046), those receiving a prescription for steroids (OR=1.90, P=.037), and those diagnosed with Parkinson disease (OR 1.58, P=.051). CONCLUSION: A substantial number of patients with dementia are being prescribed antidepressant or antipsychotic medications by their primary care practitioners without evidence of depression or psychosis in their electronic medical records.